DC Motor Speed Control Using Microcontroller PIC 16F877A - Muhammad Shahril, Abu Bakar (UTeM, 2009)

(untitled)
Direct current (DC) motor has already become an important drive configuration for many applications across a wide range of powers and speeds. The ease of control and excellent performance of the DC motors will ensure that the number of applications using them will continue grow for the foreseeable future. This project is mainly concerned on DC motor speed control system by using microcontroller PIC 16F877 A. It is a closed-loop real time control system, where optical encoder (built in this project) is coupled to the motor shaft to provide the feedback speed signal to controller. Pulse Width Modulation (PWM) technique is used where its signal is generated in microcontroller. Microcontroller acts as proportional (P) controller with Kp =1 in this study. The PWM signal will send to motor driver to vary the voltage supply to motor to maintain at constant speed. Besides, it also shows a graph of motor speed versus time to let the user monitor the performance of the system easily. Based on the result, the reading of tachnometer built is quite reliable. Through the project, it can be concluded that microcontroller PIC 16F877 A can control motor speed at desired speed although there is a variation of load.